2012
DOI: 10.1080/14733285.2012.667916
|View full text |Cite
|
Sign up to set email alerts
|

‘It came up to here’: learning from children's flood narratives

Abstract: The growing body of literature that seeks to understand the social impacts of flooding has failed to recognise the value of children's knowledge. Working with a group of floodaffected children in Hull using a storyboard methodology this paper argues that the children have specific flood experiences that need to be understood in their own right. In this paper we consider the ways in which the disruption caused by the flood revealed and produced new -and sometimes hidden -vulnerabilities and forms of resilience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…Other youth-based climate engagement work conducted in Australia, Europe, and North America supports this framework (Arnold, Cohen, & Warner;De Vreede, Warner, & Pitter, 2014;Hickman, 2012;Reinfried, Rottermann, Aeschbacher, & Huber, 2010), and in particular, the importance of localized, solutions-based approaches with positive messaging (Percy-Smith & Burns, 2012). The works of Paschen and Ison (2013) and Walker et al (2012) on climate narrative demonstrate similar opportunities for engagement to provide new knowledge with regard to vulnerability and resilience as experienced by local community members, as does the work of Haynes and Tanner (2015) which explores the role of participatory video as an alternative methodology for community generated digital storytelling that shares youth experiences of climate-related disasters. Collectively, these engagement techniques suggest a powerful opportunity in the employment of digital and social media: social media enables the sharing of personal narratives, supports experiential learning, engages with existing online social activity of today's youth, and promotes peer-to-peer interaction (Corner & Roberts, 2014a, 2014bSenbel, Ngo, & Blair, 2014).…”
Section: Youth Participation In Planningmentioning
confidence: 99%
“…Other youth-based climate engagement work conducted in Australia, Europe, and North America supports this framework (Arnold, Cohen, & Warner;De Vreede, Warner, & Pitter, 2014;Hickman, 2012;Reinfried, Rottermann, Aeschbacher, & Huber, 2010), and in particular, the importance of localized, solutions-based approaches with positive messaging (Percy-Smith & Burns, 2012). The works of Paschen and Ison (2013) and Walker et al (2012) on climate narrative demonstrate similar opportunities for engagement to provide new knowledge with regard to vulnerability and resilience as experienced by local community members, as does the work of Haynes and Tanner (2015) which explores the role of participatory video as an alternative methodology for community generated digital storytelling that shares youth experiences of climate-related disasters. Collectively, these engagement techniques suggest a powerful opportunity in the employment of digital and social media: social media enables the sharing of personal narratives, supports experiential learning, engages with existing online social activity of today's youth, and promotes peer-to-peer interaction (Corner & Roberts, 2014a, 2014bSenbel, Ngo, & Blair, 2014).…”
Section: Youth Participation In Planningmentioning
confidence: 99%
“…Children's experiences are crucial for promoting resilience in all stages: preparing for disasters, responding, and recovering. Some of the more recent studies have focused on children who have experienced living through disasters, understanding their perceptions and promoting their recovery through art, music, photography, videography, and other tools (Walker et al 2012;Bonati and Mendes 2014;Fothergill and Peek 2015;Freeman et al 2015;Fletcher et al 2016;Cox et al 2017). Other studies take children as a group in context, whose collective action in their familiar settings (household, neighborhood, and school) and their wider (online and offline) networks can generate agency and action benefiting their communities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Older people may be the most affected by the loss of memorabilia collected over a lifetime (Tapsell et al 1999, Thrush et al 2005b, they are also over-represented amongst residents of bungalows, ground floor flats and mobile homes, property types that tend to involve a greater degree of damage to possessions due to a shortage of dry storage space (Tapsell et al 1999;Ketteridge and Fordham 1998). At the other end of the age spectrum, research in Hull with children has shown that they can experience distinct physical health symptoms (predominantly exacerbation of asthma) and stress, related both to their own situation and the pressures on adults around them (Walker, M et al 2010) and various forms of loss -the immediate loss of tangible things such as toys, games and photographs, but also in the extended aftermath of the flood the loss of space, privacy, special events and time with family and friends.…”
Section: Patterns Of Vulnerability To Flood Impactsmentioning
confidence: 99%
“…In moving through these key questions we review and examine the UK situation and the body of existing research literature on UK flood experience that can be used to begin to fill out our understanding and analysis -including research that we have undertaken for the Environment Agency and a recent project on the impacts of a major flood in the City of Hull in 2007 , Walker et al 2010. Whilst flooding has not been systematically examined as an environmental justice issue in the UK, there is a limited body of work that has analysed patterns of social distribution and fairness in flood management, and a more substantial literature focused on questions of vulnerability to flooding.…”
Section: Introductionmentioning
confidence: 99%